PENGUATAN BUDAYA ORGANISASI MELALUI SISTEM PENGENDALIAN MANAJEMEN UNTUK MENINGKATKAN KINERJA HOTEL - Arviana, Nerissa; Daromes, Fransiskus Eduardus; Kampo, Kunradus (Jurnal Akuntansi Kontemporer, 2021)
This study explains that management control system is a mechanism to encourage the strengthening of organizational culture in enhancing hotel performance. The study used a survey method through questionnaires on managers and heads of departments at 3, 4, and 5-star hotels Makassar. Data analysis was performed by path analysis and Sobel test. The results show that organizational culture has no direct effect on hotel performance, however, it has a positive and significant effect on the management control system, which in turn has a positive and significant effect on hotel performance. In other words, management control system mediates the influence of organizational culture on hotel performance.